Molecular signature of the Neoproterozoic Acraman impact event - Hallman, Christian; Grey, K.; Webster, L.; McKirdy, D.; Grice, Kliti (Elsevier Science, 2010)
The Neoproterozoic era witnessed at least two severe glaciations and the first emergence of animal phyla. Understanding the triggers for these events relies on the global contextualisation of the prevailing environmental conditions. This in turn requires a solid chronostratigraphic framework which, as yet, remains fragmentary. Here we show that late Neoproterozoic (Ediacaran) marine sediments in the Officer Basin, Australia, deposited during and after a bolide impact (the Acraman event), contain enhanced concentrations of the polycyclic aromatic hydrocarbon coronene, which can be produced by the combustion of biomass. The coincidence of the coronene anomaly with a negative sedimentary carbon isotopic excursion suggests a relationship to combustion processes induced by the Acraman impact. Coronene occurrence at a distance beyond granular impact ejecta, as well as analogies of accompanying phenomena with those linked to the aftermath of the Cretaceous-Tertiary (K-T) extinction event, indicate that pyrogenic compounds formed during the Acraman event are likely to have been deposited across a geographically extensive area. This could provide a valuable chronostratigraphic marker in the form of an Ediacaran molecular ash bed.